Fenomena Perekonomian Dalam Novel “Negeri Para Bedebah” Karya Tere Liye - Merliyana Wulan Ndari; Itrah Nur Mahdiyyah; Eva Dwi Kurniawan (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
The novel Negeri Para Bedebah by Tere Liye is a novel that contains Accounting Theory. This research aims to analyze economic phenomena. The data used was taken from reading the novel Negeri Para Bedebah using a descriptive approach and qualitative methods. The novel contains about fraud and manipulation of financial reports at Bank Semesta. The results of this research include asset valuation, interest rates, inflation and the purchasing power of money